Faktorer som virker inn ved frafall i døgnbehandling for pasienter med ruslidelser. En case studie med vekt på både pasient- og behandlerperspektivet - Ormbostad, Helga A. K.; Dale, Karl Yngvar; Gjengedal, Eva Johanne; Stallvik, Marianne (Nordisk tidsskrift for helseforskning, 2017)
Factors affecting dropout from residential treatment for patients with substance use disorders. A case study with emphasis on both patient and clinician perspectives Retention in substance abuse treatment is one of the most consistent predictors of successful treatment. Despite dropout rates from 17-57% for inpatient treatment, little is known of potential risk factors related to treatment programs and processes. The aim of this study is to obtain knowledge of this phenomenon by studying underlying processes and conditions associated with dropout. The Case study method is chosen because of the scant literature and the ability of this method to gain in-depth information. The data material consists of qualitative interviews of patients and clinical staff together with journal material. The results indicate complex conditions associated with attrition and that the patients left treatment despite positive experiences and perceived usefulness of the program. It is suggested that there might be a process prior to the decision of leaving and that special attention should be paid to patients at higher risk for dropout.